Stereoscopic Architectural Photography and Merleau-Ponty’s Phenomenology - Klahr, Douglas M. (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
Stereoscopic photography utilizes dual camera lenses that are placed at approximately the interocular distance of human beings in order to replicate the slight difference between what each eye sees and therefore the effect of parallax. The pair of images that results is then viewed through a stereoscope. By adjusting the device, the user eventually sees the two photographs merge into a single one that has receding planes of depth, often producing a vivid illusion of intense depth. Stereoscopy was used by photographers throughout the second half of the Nineteenth Century to document every building that was deemed to be culturally significant by the European and American photographers who pioneered the medium, starting with its introduction to the general public at the Crystal Palace in London in 1851. By the early 1900s, consumers in Europe and America could purchase from major firms stereoscopic libraries of buildings from around the world. Stereoscopic photography brought together the emotional, technical and informed acts of looking, especially with regard to architecture. In this essay, the focus in upon the first of those acts, wherein the phenomenal and spatial dimensions of viewing are examined. Images of architecture are used to argue that the medium not only was a manifestation of Maurice Merleau-Ponty’s phenomenology of perception, but also validated the philosophy. After an analysis of how stereoscopic photography and Merleau-Ponty’s philosophy intersect, seven stereographs of architectural and urban subjects are discussed as examples, with the spatial boundaries of architecture and cities argued as especially adept in highlighting connections between the medium and the philosophy. In particular, the notion of Fundierung relationships, the heart of Merleau-Ponty phenomenology, is shown to closely align with the stereoscopic viewing experience describing layers of dependency.
Keywords: Stereoscopy; Photography; Architecture; Merleau-Ponty; Fundierung; Cities